Perceptions and Practices of Therapeutic Hypothermia in American Neonatal Intensive Care Units - Harris, Malinda N.; Carey, William A.; Ellsworth, Marc A.; Haas, Lindsey R.; Hartman, Tyler K.; Lang, Tara R.; Colby, Christopher E. (American Journal of Perinatology, 2014)
Objective In 2005, therapeutic hypothermia (TH) was used in few American neonatal intensive care units (NICUs) with great variability in practices. We hypothesized that TH would be used with greater frequency and uniformity today.Study Design We surveyed directors of 797 NICUs queried in our prior study to determine attitudes toward and practices of TH.Results Of the 781 participants with valid addresses, we received completed surveys from 330 (42.3%). There was an increase in the number of respondents who believed that TH is effective (85% versus 31%, p < 0.0001). More NICUs used TH (50% versus 6%, p < 0.0001) and nearly all not offering TH transferred eligible neonates to centers that did (97% versus 29%, p < 0.0001). There has been increased standardization of TH practices with regard to enrollment criteria, duration, and methods of monitoring.Conclusion TH has become standard of care for the treatment of HIE in the United States. Most NICUs that use TH adhere to protocols, but variation still exists in TH practices.
Keywords: induced hypothermia; hypoxic-ischemic encephalopathy; neonatal intensive care units